2021
DOI: 10.1093/toxres/tfab041
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin nicotinate suppresses abdominal aortic aneurysm pyroptosis via lncRNA PVT1/miR-26a/KLF4 axis through regulating the PI3K/AKT signaling pathway

Abstract: Abdominal aortic aneurysm (AAA) is a chronic dilated disease of the aorta that is characterized by chronic inflammation. Curcumin (Cur) is previously showed to attenuate AAA by inhibiting inflammatory response in ApoE −/− mice. Since Cur has the limitations of aqueous solubility and instability. Here, we focus on the role of curcumin nicotinate (CurTn), a Cur derivative is derived from Cur and nicotinate. An in vitro model of AAA was established by treating vascular smooth muscle cells (VSMCs) with II (Ang-II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This process is accompanied by the release of many inflammatory factors such as IL‐1β and IL‐18, which ultimately magnifies the local inflammatory response. Xiong et al found that regulation of vascular smooth muscle cell pyroptosis could constrain AAA [ 46 ]. Moreover, macrophage pyroptosis has been suggested to be involved in AAA [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process is accompanied by the release of many inflammatory factors such as IL‐1β and IL‐18, which ultimately magnifies the local inflammatory response. Xiong et al found that regulation of vascular smooth muscle cell pyroptosis could constrain AAA [ 46 ]. Moreover, macrophage pyroptosis has been suggested to be involved in AAA [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our data, KLF4 upregulation increased the levels of oxidative stress markers and proinflammatory cytokines in LPS-treated ATDC5 cells in ankylosing spondylitis (52), and KLF4 deficiency imparts an anti-inflammation role in dextran sodium sulfate–triggered colitis (53). Moreover, decreased KLF4 expression diminishes pyroptosis of Ang-II–treated vascular smooth muscle cells by blocking the PI3K/AKT signaling pathway (54). Collectively, the above evidence indicated that KLF4 upregulation neutralized the suppression of silencing USP25 on pyroptosis in AP induced by LPS and CRE.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we explored the molecular mechanism underlying PVT1-mediated AAA progression in the H 2 O 2 induced VSMCs injury model. In an in vitro model of AAA, PVT1 knockout not only inhibited VSMC apoptosis and ECM disruption, but also suppressed VSMC pyroptosis and inflammation [ 22 , 23 ]. We also found that the high expression of PVT1 in AAA tissues and PVT1 silencing increased VSMC proliferation, blunted the apoptosis rate, and alleviated inflammatory events in the H 2 O 2 -induced apoptotic model of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Xiong et al . also reported that the promotion of AAA by PVT1 is mediated by the miR-26a/KLF4 axis through the PI3K/AKT signaling pathway [ 23 ]. In contrast, NCKAP1L loss blunts AKT phosphorylation and modulates immunodeficiency [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation